TIMORESE LANGUAGE STUDENTS’ LEVELS OF METACOGNITIVE AWARENESS OF READING STRATEGIES - Manuel Mendonca Araujo; Concilianus Laos Mbato (Magister Scientiae, 2023)
Reading strategies are crucial in education. This research focused on Timorese language students’ levels of reading strategies. It attempted to answer two research questions; (1) What are the levels of Timorese language students’ metacognitive awareness of reading strategies? and (2) How do Timorese language students apply the reading strategies in their reading experiences? A mixed-method design was adopted. Mokhtari & Sheorey’s (2002) Survey of Reading Strategies (SoRS) was used to collect quantitative data. The findings revealed two high levels; global reading strategies, with a mean value M=3.86, SD=1.1837, and support reading strategies, with a mean value of M=3.79 SD=1.2120. Problem-solving strategies were medium-level, with a mean value M=3.61, SD=1.1718. Highlighting keynotes, using google, discussing, controlling speed were revealed in the qualitative data as adopted reading strategies. Language teachers could use this research to improve language students’ reading strategies, and future researchers should do extensive research to provide more findings.   Keywords: awarenes, metacognitive, reading strategies.